2020
DOI: 10.1108/caer-12-2018-0239
|View full text |Cite
|
Sign up to set email alerts
|

How does farmers' field schooling impact eco-efficiency? Empirical evidence from paddy farmers in Bangladesh

Abstract: PurposeRecent studies suggest extensive use of environmental resources in agrofarming degrades ecosystem significantly. In this backdrop, this study aims at assessing ecoefficiency of paddy farming. Because ecoefficiency links up between economic performances and environmental resources supporting the provision of goods and services for the society, this study further investigates the effectiveness of attending Farmers' Field School … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…The environmental index of -0.75 also demonstrates a concerning trend of farmers' limited awareness regarding the harmful effects of pesticide misapplication on the environment, including soil organisms and water contamination. This observation aligns with research by Carbajal-Hernández et al (2022), Islam et al (2020), Khan andDamalas, (2014), andYayra Fosu-Mensah et al (2022) emphasizing the need to educate farmers about the environmental impacts of pesticide use to promote sustainable agricultural practices.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The environmental index of -0.75 also demonstrates a concerning trend of farmers' limited awareness regarding the harmful effects of pesticide misapplication on the environment, including soil organisms and water contamination. This observation aligns with research by Carbajal-Hernández et al (2022), Islam et al (2020), Khan andDamalas, (2014), andYayra Fosu-Mensah et al (2022) emphasizing the need to educate farmers about the environmental impacts of pesticide use to promote sustainable agricultural practices.…”
Section: Resultssupporting
confidence: 88%
“…In addition to its human health impact, pesticide misuse has severe environmental consequences (Afari--Sefa et al, 2015;Zhou et al, 2020). Pesticides contaminate soil, bodies of water, and the air, leading to the death of beneficial organisms like pollinators and soil microorganisms essential for plant growth (Islam et al, 2020;Khan and Damalas, 2014;. Furthermore, the development of pesticide-resistant pests and pathogens reduces the effectiveness of pest control strategies, necessitating increased pesticide use and leading to further environmental damage (Denkyirah et al, 2016;Flower et al, 2004;González-Andrade et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Ullah et al (2019) recommended the need of agricultural extension services among the farmers to adopt new technologies and enhance the managerial skills. Recently, Islam et al (2020) examined the efficiency of paddy farmers of Bangladesh and suggested that the available training programs were useful to improve the efficiency for better agricultural production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eco-efficiency is used to measure sustainability by looking at achieving economic and environmental targets [35]. Ecoefficiency is the ratio between added economic value and environmental load during a specific period [36]- [38]. Ecoefficiency analyzes complex ecosystems' economic, resource, and environmental inputs and outputs [37].…”
Section: Introductionmentioning
confidence: 99%